Characteristics and applications of some dolomitic rocks from Argentina - Marfil, Silvina Andrea (2017)
Argentina is a vast territory with different geological settings. In this scenery, dolomitic rocks are abundant and widespread. The economic importance of both this lithology and the main mineral constituent (dolomite) is the first cause for the studies carried out on these types of rocks. Dolomitic rocks in Argentina have been exploited for hundreds of years for different purposes. They are used as refractories, concrete aggregates and mastics, among other applications. Marble processing varies depending on its use and could include chemical treatments, burning, crushing, milling, and polishing. More impure marbles are crushed and used for construction, or discarded in spoil heaps in quarries. This chapter describes the mineralogical characteristics, textures, origin, mineral assemblages, and application of some dolostones, calcitic dolostones, dolomitic limestones, and marbles from the provinces of Buenos Aires, Río Negro and Córdoba (Argentina). The origin of these rocks varies even in close areas. In the province of Río Negro there are several deposits. One of them is composed of a dolostone formed from a preexisting hydrothermal limestone by circulation of hypersaline fluids rich in Mg and Na. It is a porous fine-grained (10 to 30 µm) rock consisting of dolomite with minor amounts of quartz, feldspar, and rhyolite particles. Clay minerals (montmorillonite, illite and sepiolite) were also identified. The alkali–carbonate reactivity of this rock when used as concrete aggregate has been analyzed. Another deposit is composed of a dolomitic marble generated by the metamorphism of a preexisting dolostone. The only mineral present is dolomite, but the further circulation of hydrothermal fluids in cracks developed talc veins with a sepiolite + calcite + amphibole (tremolite) assemblage. The main use of this rock is in mastics and refractories. The dolomitic limestone from the province of Buenos Aires is a compact medium–to– coarse–grained (1500 to 4500 µm) rock, consisting of calcite, dolomite and minor amount of quartz. This type of rock is one of the most important materials in the area used as concrete aggregate. In the province of Córdoba, marbles appear as lens or tabular banks with different metamorphic grades associated with gneisses, migmatites, amphibolites, and ultramafic rocks. Their composition is variable, where calcitic to dolomitic end members are recognized. The content and type of accessory minerals are also variable depending on the initial composition of the protolith, the metamorphic grade achieved, and secondary hydrothermal processes. In the Altautina area, marbles are mainly dolomitic to calc– dolomitic, minerals of the amphibole group being one of the main accessories (with some asbestiform varieties). These rocks are crushed and used for construction, or discarded in spoil heaps in quarries.